Providing Structured Real-Time Feedback on Postdischarge Outcomes Using Electronic Health Record Data. Issue 3 (March 2023) - Zegarek, Matthew H.; Holleck, Jürgen L.; Merchant, Naseema; Windish, Donna M.; Hay, Seonaid
Abstract : Feedback on postdischarge patient outcomes is lacking in both undergraduate and graduate medical education and is needed to develop trainee competence in orchestrating transitions of care. The authors describe a brief, low-resource intervention delivered to medical students and internal medicine residents at the end of an inpatient internal medicine rotation. During the session, facilitators reviewed postdischarge outcomes obtained from the electronic health record, fostered self-reflection, and coached to develop goals for future practice. The authors assessed the impact on both trainee and faculty knowledge and attitudes. Abstract: Objectives: Most trainees do not receive information about postdischarge outcomes, despite the importance of external feedback for accurate self-assessment and improvement in discharge planning skills. We aimed to design an intervention to foster reflection and self-assessment by trainees regarding how they can improve transitions of care with minimal investment of program resources. Methods: We developed a low-resource session delivered near the end of an internal medicine inpatient rotation. Faculty, medical students, and internal medicine residents reviewed and reacted to postdischarge outcomes of their patients, explored understanding of the reasons for these outcomes, and developed goals for future practice. The intervention required minimal resources given that it was conducted during scheduled teaching time, did not require additional staff, and used already available data. Forty internal medicine resident and medical student participants completed pre- and postintervention surveys that evaluated their understanding of causes for poor patient outcomes, sense of responsibility for postdischarge outcomes, degree of self-reflection, and goals for future practice. Results: Trainee understanding of the causes for poor patient outcomes was significantly different in several areas after completing the session. Trainees were less likely to believe that their responsibility for patients ends at the time of discharge, indicating an increase in sense of responsibility for postdischarge outcomes. After the session, 52.6% of trainees planned to change their approach to discharge planning, and 57.1% of attending physicians planned to change their approach to discharge planning with trainees. Through free-text responses, trainees noted that the intervention facilitated reflection and discussion about discharge planning and led to the development of goals to adopt specific behaviors for future practice. Conclusions: Meaningful information about postdischarge outcomes from the electronic health record can be used to provide feedback to trainees in a brief, low-resource session during an inpatient rotation. This feedback significantly affects trainee sense of responsibility for and understanding of postdischarge outcomes, which may lead to improved trainee ability to orchestrate transitions of care.